The Role Of The Camat In The Era Of Regional Autonomy - Muhammad Suhardi (International Journal of Scientific Research, 2025)
This paper aims to examine and analyze the role of the Camat (Sub-district Head) in the era of Regional Autonomy, focusing on their position as the spearhead of governance at the sub-district level. This study adopts a normative-prescriptive approach, seeking arguments from research findings to assess what is right or wrong and to formulate what should be according to the law. In analyzing the Camat's role, Soekanto's concept of Role is employed, which highlights the Camat's position in carrying out their rights and obligations, including the authority vested in them. Based on this analysis, it is found that the Camat holds a highly strategic position within the regional government structure, acting as a direct liaison between the district/city government and the community at the sub-district level. However, this strategic position also brings dilemmas. On one hand, the Camat is expected to perform coordination, supervision, and guidance functions for village/urban village apparatus while implementing policies set by the regional government. On the other hand, the Camat often faces limitations in resources, whether in terms of budget, authority, or administrative support, which can affect the optimization of their role. Thus, the Camat's role in the era of Regional Autonomy is crucial yet challenging. Strengthening capacity and clarifying regulations are necessary to support the Camat in carrying out their duties and functions effectively and efficiently.